Subtitling for the deaf and the hard-of-hearing —A learning service approach at the audiovisual translation classroom - Tamayo, Ana (Íkala, Revista de Lenguaje y Cultura, 2016)
Nowadays, within didactics in Translation, acquiring interpersonal competence plays a key role in training future audiovisual translators. With the aim of developing such interpersonal competence, the author has introduced an educational innovation project in the field of audiovisual accessibility training, more specifically in the field of subtitling for the D/deaf and the Hard-of-Hearing (SDH). This action-research project is based on the service-learning methodology, which allows providing a social service while students acquire academic knowledge. This paper presents the advantages in the field of audiovisual accessibility training that derive form this educational action.